The Christmas pig - Rowling, J. K. (Scholastic Inc., 2021)
"Jack loves his childhood toy, Dur Pig. DP has always been there for him, through good and bad. Until one Christmas Eve something terrible happens -- DP is lost. But Christmas Eve is a night for miracles and lost causes, a night when all things can come to life ... even toys. And Jack's newest toy -- the Christmas Pig (DP's replacement) -- has a daring plan: Together they'll embark on a magical journey to seek something lost, and to save the best friend Jack has ever known ..."--